Data mining application to decision-making processes in university management - García, Juan Carlos (2007)
This article aims at identifying and characterizing the different configurations of the relevant factors related to administrative procedures, in order to learn about their behavior, and so about decision-making processes. Delays in administrative circuit concretion, users dissatisfaction and lack of autonomy are among the problematics leading to the diagnosis of the situation, so as to detect the elements playing key parts in said scenario. Data analyzed was collected from files and notes submitted by the middle management, i.e., pedagogical areas and departments at a Higher Education institution in Argentina, the School of Economic and Social Sciences, FCEyS, of the Universidad Nacional de Mar del Plata, UNMDP, throughout 2002 - 2005. Knowledge acquired through data mining techniques in their character of strategic knowledge, turns out to be potentially useful in the diagnosis of administrative circuit problematics in university environments. Besides, it is particularly beneficial in institutional decision-making processes, promoting plan of action deigns for an efficacious administrative management.